US Military Bases and Anti-Military Organizing: An Ethnography of an Air Force base in Ecuador - Fitz-Henry, Erin (Palgrave Macmillan, 2020)
US military presence in twenty-first century in Latin America has recently been characterised by rapidly intensifying militarization alongside under-supported anti-military activism. This book redirects recent debates about twenty-first century social mobilization by taking seriously those who actively resist the social movements in their midst